1999
DOI: 10.1073/pnas.96.20.11637
|View full text |Cite
|
Sign up to set email alerts
|

The unseen color aftereffect of an unseen stimulus: Insight from blindsight into mechanisms of color afterimages

Abstract: We show here that, in the absence of a direct geniculostriate input in human subjects, causing loss of sight in the visual half-field contralateral to the damage, the pupil responds selectively to chromatic modulation toward the long-wavelength (red) region of the spectrum locus even when the stimulus is isoluminant for both rods and cones and entirely restricted to the subjects' ''blind'' hemifields. We also show that other colors are less or wholly ineffective. Nevertheless, red afterimages, generated by chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In humans, there is indirect evidence that only the RTVS preserves this reptilian-like dichromatic color encoding program, as the SC is insensitive to other color signals such as those mediated by the S-cone (blue/yellow color spectrum) [21]. Thus, in patients with hemifield blindsight, meaning a hemifield deficiency of the V1-mediated trichromatic vision but with intact hemifield function of the RTVS, the pupil continues to react selectively to red stimuli, even when the stimulus is isoluminant for both rods and cones and entirely restricted to this "blind" hemifield [81]. In contrast, PD patients show significant impairment of color discrimination, especially in the red/green spectrum (along the protan and deutan axes), while the impairment of the tritan axis is considered to be an independent aging phenomenon [69].…”
Section: Phylogenetic Considerations On Visual Impairmentmentioning
confidence: 96%
“…In humans, there is indirect evidence that only the RTVS preserves this reptilian-like dichromatic color encoding program, as the SC is insensitive to other color signals such as those mediated by the S-cone (blue/yellow color spectrum) [21]. Thus, in patients with hemifield blindsight, meaning a hemifield deficiency of the V1-mediated trichromatic vision but with intact hemifield function of the RTVS, the pupil continues to react selectively to red stimuli, even when the stimulus is isoluminant for both rods and cones and entirely restricted to this "blind" hemifield [81]. In contrast, PD patients show significant impairment of color discrimination, especially in the red/green spectrum (along the protan and deutan axes), while the impairment of the tritan axis is considered to be an independent aging phenomenon [69].…”
Section: Phylogenetic Considerations On Visual Impairmentmentioning
confidence: 96%
“…Sahraie and Barbur (1997) observed pupil constriction when incoherent moving random dots were physically switched to a coherent motion flow, and they observed a reduction of this constriction for patient GY when the stimuli were presented in his blind hemifield. Barbur et al (1999) observed that the PLR to isoluminant green (but curiously, not red) stimuli was abolished in the blind hemifield of two patients with cortical lesions. Wilhelm et al (2002) observed that patients with Parinaud's syndrome, who had no pupil response to light changes, still displayed pupil constriction to gratings and isoluminant red stimuli.…”
Section: Perceptual Bistability and Pupil Responsementioning
confidence: 96%
“…Well-studied examples of pupil dilations in response to non-sensory processing comprise cognitive load (Beatty & Wagoner, 1978;Kahneman & Beatty, 1966), attention (Beatty, 1977), stimulus probability (Reinhard & Lachnit, 2002), and emotional factors (Partala & Surakka, 2003). In addition, changes of pupil size have been observed for specific visual computations supposed to involve the visual cortex, like the transition from incoherent to coherent motion (Sahraie & Barbur, 1997), color perception (Barbur, Weiskrantz, & Harlow, 1999;Wilhelm, Wilhelm, Moro, & Barbur, 2002), or the processing of faces (Conway, Jones, DeBruine, Little, & Sahraie, 2008), raising the possibility that pupil dynamics reflects some aspects of cortical processing.…”
Section: Introductionmentioning
confidence: 97%
“…There is still no consensus about whether the feelings associated with type 2 blindsight are always indicative of a visual phenomenology, or whether they sometimes arise through the exercise of the blindsighters' ability to identify visual stimuli (Brogaard, 2012;Overgaard & Grünbaum, 2011). If the phenomenology is associated with the experimental task, the residual awareness may be cognitive and high-level rather than perceptual and low-level (Barbur, Weiskrantz, & Harlow, 1999;Brogaard, 2011aBrogaard, , 2011bBrogaard, 2012;Kentridge & Heywood, 1999;Sahraie et al, 1997). GY's use of the word 'feeling' might also suggest that the phenomenology is similar to that of certain affective states.…”
Section: Type 2 Blindsightmentioning
confidence: 94%